Análisis Financiero A La Empresa “Proinvi S.A” En El Período 2014-2015. Propuesta De Mejoramiento - Sarango Salvay, Andrea del Rosario (2018)
The present thesis work entitled "FINANCIAL ANALYSIS TO THE COMPANY" PROINVI S.A "IN THE PERIOD 2014-2015. PROPOSAL FOR IMPROVEMENT. "It was developed with the purpose of knowing and analyzing the economic and financial situation of the company, allowing the partners to make adequate decisions for the benefit of the company. In order to meet the specific objectives, the degree of participation of each of the accounts of the financial statements was determined in relation to the group and subgroup to which they belong, coming to know the economic and financial structure in a vertical way; A comparative analysis was then carried out to establish the increases and decreases in the accounts from one period to another as a result of the operations carried out in the years 2014 and 2015. Once the vertical and horizontal analysis is carried out, the financial indicators are calculated to measure the company's performance and financial situation, indicating that the company does not have sufficient liquidity to cover its short and long-term debts; Within the Activity indicators it is evident that the asset turnover is slow, the recovery of accounts receivable is not satisfactory; Applying the indicators of Indebtedness it was 5 known that the company is not in the capacity to cover its liabilities and assume new debts; Through the profitability indicators it was determined that the generation of yields are not satisfactory since they do not compensate as they would wish the investment made. The performance obtained was also checked by the Dupont System. At the end of the thesis work, it was concluded that the company "Proinvi" does not apply the financial analysis carried out by the External Audit, allowing it to know the economic and financial position of the same, which deserves to recommend to the partners to apply the financial analysis at the end of each financial year, so that the results can be compared with previous years and thus have clear and timely information to facilitate decision making.